Microvessels Density in Uterine Leiomyosarcoma. (16th June 2015) - Bobiński, Marcin; Bednarek, Wiesława; Szumiło, Justyna; Cybulski, Marek; Polak, Grzegorz; Kotarski, Jan
Abstract : Uterine leiomyosarcomas (LMS) are rare tumors typically presenting rapid growth and unfavorable outcome. Nowadays the results of uterine LMS treatment do not meet expectations. Angiogenesis is one of processes investigated to be target for future treatment. The aim of the research was to assess microvessels density (MVD) in tumor samples collected from 50 patients with histological confirmed uterine leiomyosarcoma and to investigate statistical relations between MVD, patients survival, and FIGO stage of tumor. The assessment was carried out using immunohistochemistry methods with anti-CD34 antibody. No significant difference in MVD between FIGO stages was observed. Furthermore, contrary to many other malignancies, we found no significant relation between MVD and patients overall and 2-year survival. Results obtained in the study suggest that processes on vascular mimicry and mesenchymal to epithelial transition (MET) may play important role in development of LMS. No statistical relation between MVD and survival leads to conclusion that not only angiogenesis but other mechanisms as well should be taken into consideration in planning future research.